2011
DOI: 10.1038/ncb2313
|View full text |Cite
|
Sign up to set email alerts
|

Notch post-translationally regulates β-catenin protein in stem and progenitor cells

Abstract: Cellular decisions of self-renewal or differentiation arise from integration and reciprocal titration of numerous regulatory networks. Notch and Wnt/β-Catenin signaling often intersect in stem and progenitor cells and regulate one another transcriptionally. The biological outcome of signaling through each pathway often depends on the context and timing as cells progress through stages of differentiation. Here, we show that membrane-bound Notch physically associates with unphosphorylated (active) β-Catenin in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
244
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(262 citation statements)
references
References 40 publications
(46 reference statements)
13
244
2
1
Order By: Relevance
“…Interference with Notch signaling arrests cardiac development (6,(23)(24)(25). In accordance, MesP1-cre-induced mutation of RBPJ lox/lox (hereafter, "RBPJ mutant") reduced the size and compactness of the heart, as revealed by analyses of H&E-stained sections at embryonic day (E) 9.75 ( Fig.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Interference with Notch signaling arrests cardiac development (6,(23)(24)(25). In accordance, MesP1-cre-induced mutation of RBPJ lox/lox (hereafter, "RBPJ mutant") reduced the size and compactness of the heart, as revealed by analyses of H&E-stained sections at embryonic day (E) 9.75 ( Fig.…”
Section: Resultsmentioning
confidence: 78%
“…In previous analyses of mice that carried a conditional Jagged1 mutation or that expressed a dominant-negative Maml using Mef2c-cre also exhibit SHF morphogenesis affects and reduced Bmp and Fgf signaling (23). In contrast, in studies using Isl1-cre, elevated Wnt/ β-catenin signaling has been observed after conditional mutation of Notch1 but not RBPJ (24,25). The difference in phenotypes might be caused by the use of distinct cre lines to target cardiac cells or by effects that are not mediated by canonical Notch signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was shown that membrane-associated uncleaved Notch directly interacts with -catenin, serving as a protein trap and downregulating the cellular levels of -catenin. This process has been demonstrated to require the endocytic adaptor protein Numb and lysosomal activity [475]. In turn, the Notch ligand Jag1, which is a target of Wnt/ -catenin signaling, functions as a Wnt-dependent Notch activator [476].…”
Section: Interconnections Between Notch and -Catenin Signalingmentioning
confidence: 99%
“…Accumulating evidence has underlined the importance of the mutually inhibitory cross-talk between Wnt and Notch pathways (11)(12)(13)(14)(15)(16)(43)(44)(45). In injured skeletal muscle, Notch and Wnt exert opposing influences on proliferation and differentiation of progenitor cells, respectively, as illustrated in studies by Brack et al using cultured muscle satellite cells (4).…”
Section: Discussionmentioning
confidence: 94%
“…The molecular mechanisms that underlie these opposing actions are incompletely understood. Notch signaling activates GSK3␤ (4) and reduces ␤-catenin levels through post-translational mechanisms (43). Conversely, Wnts down-regulate Notch expression (44) and have been found through undefined mechanisms to support Numb expression and promote cell fate determination in hepatic progenitor cells (45).…”
Section: Discussionmentioning
confidence: 99%